The Effect of Modified Porcine Surfactant Alone or in Combination with Polymyxin B on Lung Homeostasis in LPS-Challenged and Mechanically Ventilated Adult Rats - Kolomaznik, Maros (Molecules, 2020)
The study aimed to prove the hypothesis that exogenous surfactant and an antibiotic polymyxin B (PxB) can more effectively reduce lipopolysaccharide (LPS)-induced acute lung injury (ALI) than surfactant treatment alone, and to evaluate the effect of this treatment on the gene expression of surfactant proteins (SPs). Anesthetized rats were intratracheally instilled with different doses of LPS to induce ALI. Animals with LPS 500 μg/kg have been treated with exogenous surfactant (poractant alfa, Curosurf(®), 50 mg PL/kg b.w.) or surfactant with PxB 1% w.w. (PSUR + PxB) and mechanically ventilated for 5 hrs. LPS at 500 μg/kg increased lung edema, oxidative stress, and the levels of proinflammatory mediators in lung tissue and bronchoalveolar lavage fluid (BALF). PSUR reduced lung edema and oxidative stress in the lungs and IL-6 in BALF. This effect was further potentiated by PxB added to PSUR. Exogenous surfactant enhanced the gene expression of SP-A, SP-B, and SP-C, however, gene expression for all SPs was reduced after treatment with PSUR + PxB. In mechanically ventilated rats with LPS-induced ALI, the positive effect of exogenous surfactant on inflammation and oxidative stress was potentiated with PxB. Due to the tendency for reduced SPs gene expression after surfactant/PxB treatment topical use of PxB should be considered with caution.